A Critical Assessment of Experimental Methods for Determining the Dynamic Mechanical Characteristics of Shape Memory Polymers1. Issue 8 (2nd April 2013) - Kazakevičiūtė‐Makovska, Rasa; Mogharebi, Safa; Steeb, Holger; Eggeler, Gunther; Neuking, Klaus
Abstract Experimental study of temperature‐ and frequency‐dependent properties of the commercially available shape memory polymer Tecoflex™ EG 72D (TFX) (Lubrizol, USA) using dynamic mechanical analysis (DMA) technique is presented. Temperature scan DMA tests have been carried out in three distinct deformation modes, uniaxial tension, three‐point bending, and simple torsion, using two different testing rigs at different test parameters (frequency, strain amplitude, and heating rate) in temperatures ranging from below to above the glass transition temperature. The influence of different test parameters and some discrepancies in the temperature‐dependent storage and loss moduli (and hence the loss factor) measured by DMA in different deformation modes are discussed.